2008
DOI: 10.1021/om800315q
|View full text |Cite
|
Sign up to set email alerts
|

A Ferrocenyldiphosphene−Platinum Complex: Structural Features and Theoretical Calculations

Abstract: The ligand exchange reaction of (E)-TbtPPFc (Tbt = 2,4,6-tris[bis(trimethylsilyl)methyl]phenyl, Fc = ferrocenyl) and ethylenebis(triphenylphosphine)platinum(0) resulted in the formation of the corresponding η2-diphosphene−platinum complex in 82% yield. The molecular structure of the platinum complex was confirmed by spectroscopic and X-ray crystallographic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…340 The formation of diphosphacyclobutenes in stereospecific [2 þ 2]-cycloaddition reactions of diphosphorus (P 2 ) with alkenes has been the subject of a theoretical study. 341 Studies of the reactivity of diphosphenes have included chalcogenation reactions of kinetically-stable diphosphenes with elemental sulfur, selenium and tellurium, leading to thia-, selena-and tellura-diphosphiranes, 342 the formation of a ferrocenyldiphosphine-platinum(0) complex, 343 the formation of a C 10 P 2 cationic cage system on protonation of the diphosphene C 5 Me 5 PQPC 5 Me 5 , 344 and the formation of a kineticallystabilised diphosphene anion-radical by the one-electron reduction of the diphosphene TbtPQPTbt (Tbt ¼ 2,4,6-tris[bis(trimethylsilyl)methyl] phenyl). 345 A successful protocol has been developed for the introduction of stable phosphaalkene units into oligoalkynes, leading to compounds of types (162) and (163), a new class of p-conjugated molecules.…”
Section: P P -Bonded Phosphorus Compoundsmentioning
confidence: 99%
“…340 The formation of diphosphacyclobutenes in stereospecific [2 þ 2]-cycloaddition reactions of diphosphorus (P 2 ) with alkenes has been the subject of a theoretical study. 341 Studies of the reactivity of diphosphenes have included chalcogenation reactions of kinetically-stable diphosphenes with elemental sulfur, selenium and tellurium, leading to thia-, selena-and tellura-diphosphiranes, 342 the formation of a ferrocenyldiphosphine-platinum(0) complex, 343 the formation of a C 10 P 2 cationic cage system on protonation of the diphosphene C 5 Me 5 PQPC 5 Me 5 , 344 and the formation of a kineticallystabilised diphosphene anion-radical by the one-electron reduction of the diphosphene TbtPQPTbt (Tbt ¼ 2,4,6-tris[bis(trimethylsilyl)methyl] phenyl). 345 A successful protocol has been developed for the introduction of stable phosphaalkene units into oligoalkynes, leading to compounds of types (162) and (163), a new class of p-conjugated molecules.…”
Section: P P -Bonded Phosphorus Compoundsmentioning
confidence: 99%
“…Reaction of TbtPQPFc with Pt(Z 2 -C 2 H 4 )(PPh 3 ) 2 results in the formation of Pt(Z 2 -TbtPQPFc)(PPh 3 ) 2 . 73 The interaction of the diphosphene with the platinum was shown by DFT methods to be best described as a p-complex with donor/acceptor interaction between the PQP unit and the metal. Protonation of Cp*PQPCp* has been shown to afford 45 which may then be deprotonated to give the crystallographically-characterised 46.…”
Section: Phosphorusmentioning
confidence: 99%
“…Particularly, several diphosphenes have been synthesized by taking advantage of kinetic stabilization, and their fundamental reactivities have been investigated in detail . Diphosphenes are known to possess high reactivity even in the case of the kinetically stabilized diphosphenes and serve as good precursors for various heterocyclic compounds containing phosphorus atoms. , Hence, only a few examples have been reported for the substitution reactions on the phosphorus atom of diphosphenes while keeping the reactive PP unit . Although Jutzi et al reported that the diphosphene substituted by η 1 -pentamethylcyclopentadienyl groups (Cp*), [Cp*PPCp*], reacted with several lithium-amides or -alkyls (LiR; R = N(SiMe 3 ) t -Bu, N(SiMe 3 ) 2 , CH(SiMe 3 ) 2 , and C(SiMe 3 ) 3 ) to afford the corresponding diphosphenes [RPPCp*] or [RPPR] via the cleavage of the P−C bond, to the best of our knowledge, there has been no report on the transformation reactions of a diphosphene into another diphosphene by the functionalization of the substituent itself on the PP moiety.…”
mentioning
confidence: 99%